1980
DOI: 10.1063/1.863009
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the three-dimensional nature of unstable flow past a cavity

Abstract: The spanwise structure of the free-shear layer along the mouth of a cavity was visualized using the hydrogen bubble technique. Examination of the distortion of spanwise sheets of timelines reveals some of the features of interaction of secondary (longitudinal) and primary vorticity. The spanwise wavelength of the longitudinal vorticity ranged from a wavelength approximately the same as that between primary vortices to a wavelength about half as large. Patterns corresponding to large wavelengths were discernibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Three-dimensional natures of cavity flows have not been reported as frequently as flow oscillations. Rockwell and Knisely (5) have visualized distortion of primary spanwise vortex structures and formation of secondary streamwise vortices in a laminar cavity flow. Numerical studies on compressible turbulent flows (9)- (10) have shown strong three-dimensional distortion of the flow field and existence of streamwise vortices.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional natures of cavity flows have not been reported as frequently as flow oscillations. Rockwell and Knisely (5) have visualized distortion of primary spanwise vortex structures and formation of secondary streamwise vortices in a laminar cavity flow. Numerical studies on compressible turbulent flows (9)- (10) have shown strong three-dimensional distortion of the flow field and existence of streamwise vortices.…”
Section: Introductionmentioning
confidence: 99%
“…2 for visualization) (Rockwell and Naudascher, 1978;Rockwell and Knisely, 1980). Note that the detachment point refers to the location of an adverse (positive) pressure gradient in the main flow direction, which causes the upstream boundary layer to detach from a solid surface (Tritton, 1988).…”
Section: Recirculation Regions Enclosed By Mixing Layersmentioning
confidence: 99%
“…2; Rockwell and Naudascher, 1978;Rockwell and Knisely, 1980). The recirculation region is comprised of a large primary gyre and may contain one or more smaller, counter-rotating secondary gyres.…”
Section: Emergent Lateral Cavitiesmentioning
confidence: 99%
“…While responsive jitters and relativity of three-dimensionality are thought of as possible causes, there have been few studies treating this subject actively (e.g. [10] and [11]). Figure 3 shows the mean behaviour in the x-z plane measured by the PIV method as Re = 0.6 ×10 4 .…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…Later, Gharib [7] studied the effects of periodic disturbance introduced into the approach flow, and Gharib and Roshko [8] studied the relationship between the drag acting on the cavity and the flow pattern. On the other hand, as to the instantaneous flow field, Rockwell and Knisely [9,10] and Neary and Stephanoff [11] showed their experiments in the visualization of flow, and Lin and Rockwell [3] and Meganathan and Vakili [12] showed their experiments with a particle imaging velocimetry (PIV).…”
Section: Introductionmentioning
confidence: 99%